ATM Network Infrastructure Migration Strategy from Bank to PT XYZ - Dharmawan, Arief; Hilman, Muhammad Hafizhuddin Hilman (Scientific Journal of Informatics, 2025)
Purpose: This study addresses PT XYZ’s technical challenges in optimizing the Automatic Teller Machine (ATM) network infrastructure, which caused service disruptions and customer complaints during the initial pilot migration. The research aims to solve the network availability problem by designing a reliable migration strategy, thereby improving service quality and strengthening partnerships with banks. Methods: A qualitative case study analysis was conducted, combining stakeholder interviews with technical evaluations. The Data Center WAN zone deployment followed the waterfall methodology for structured network and security appliance implementation, while remote ATM migrations used an incremental approach. Service Level Agreement (SLA) metrics were monitored to measure performance. Result: The solution improved the ATM network average SLA from 98.31% to 99.53%. Stakeholder feedback confirmed the effectiveness of the phased migration and enhanced operational reliability. This demonstrates the benefit of direct ATM WAN network re-engineering in eliminating legacy infrastructure complexity. Novelty: The study provides actionable benchmarks for ATM network implementation, including phased migration steps combined with high availability WAN topology. The implementation and migration method presents a replicable model for similar financial institutions in emerging markets.